Research on Moral Education Affinity from the Perspective of Psychology - Jing, Zhang; Suting, Li (ETHICS IN PROGRESS, 2020)
Moral education affinity has a very important influence on the smooth development of moral education activities and the improvement of educational effectiveness. From the perspective of psychology, the needs and emotions of the educatees are its motivational mechanism, the will of the educatees is its maintenance mechanism, psychological compatibility is its guarantee mechanism, and the learning psychology of the educatees is the reinforcement mechanism. The generation of moral education affinity is the process of educators’ active interpersonal attraction, the application of positive psychological effect, the change of educatees’ attitude, and the psychological exchange and interaction between educators and educatees. The main way to cultivate moral education affinity is to fully pay attention to the needs or changes of the educatees, make efforts to stimulate and strengthen the learning motivation, maintain the main status and role of the educatees, and enhance the appeal and affinity of the educational process through the unity of knowledge and action.